"It's Almost Like They Were Happier When You Were Down": Microaggressions and Overt Hostility Against Native Americans in a Community with Gaming. Issue 2 (21st February 2017) - Senter, Mary S.; Ling, David A.
Abstract : In this article, we use qualitative data from 100 Native Americans living in mid‐Michigan to document the changing nature of interactions between whites and tribal members. The community studied has seen significant changes in the economic and social position of the tribal community thanks to two decades of successful gaming operations. We find that, while Native Americans attest to positive changes in the community, many of which originate within the tribe itself, hostile and negative attitudes on the part of whites persist. Some of these contemporary attitudes are carry‐overs of traditional anti‐Native prejudice, while others reflect a reworking of old stereotypes to reflect new realities, while maintaining an unequal racial order. Hostile attitudes are accompanied by discriminatory behavior, often in the form of microaggressions. We suggest that, while old‐fashioned racism has not disappeared, modern racism is more subtle and complex. While contemporary Native Americans react to and resist racism in a variety of ways, modern racist attitudes and the microaggressions that accompany them serve to reinforce an unequal racial status quo and the maintenance of a racial hierarchy of group positions.